Distribution of selected trace elements in the major fractions of donkey milk - F. Fantuz; S. Ferraro; L. Todini; R. Spurio; A. Fatica; F. Marcantoni; E. Salimei (Journal of Dairy Science, 2022)
ABSTRACT: The aim of this study was to evaluate the concentrations of Zn, Cu, Mn, Se, Mo, Co, Li, B, Ti, Cr, Rb, Sr, Cd, and Pb in donkey milk and their distribution in major milk fractions (i.e., fat, casein, whey proteins, and aqueous phase). Individual milk samples were provided by 16 clinically healthy lactating donkeys. Subsequent centrifugation, ultracentrifugation, and ultrafiltration were carried out to remove fat, casein, and whey proteins to obtain skim milk, a supernatant whey fraction, and the aqueous phase of milk, respectively. Concentrations of the elements were measured in whole milk and fractions by inductively coupled plasma-mass spectrometry, and the concentrations associated with fat, casein, and whey proteins were then calculated. The effect of removal of fat, casein, and whey proteins was determined by repeated-measures ANOVA. The fat fraction of donkey milk carried a small (∼4.5% to 13.5%) but significant proportion of Mo, Co, Ti, Cr, and Sr. The casein fraction in donkey milk carried almost all milk Zn, a majority of Cu and Mn, and most of Mo, Ti, and Sr. Relevant proportions, between 20% and 36%, of Se, Co, and Cr were also associated with caseins. The majority of Se, Co, Li, B, Cr, and Rb, and relevant proportions of Mn, Mo, Ti, and Sr were found in soluble form (ultracentrifuged samples) and distributed between whey proteins and the aqueous phase of milk (ultrafiltered samples). Whey proteins in donkey milk carried the majority of milk Se and Co. All Li and B was present in the aqueous phase of milk, which also contained most Rb and Cr, and 17% to 42% of Mn, Se, Mo, Co, Ti, and Sr.